2022
DOI: 10.3389/fneur.2022.970111
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and risk of stroke: A meta-analysis of randomized controlled trials

Abstract: BackgroundPrevious observational studies have supported the hypothesis that vitamin D supplementation protects against stroke. However, several current intervention studies contradict this observation. Therefore, we conducted a meta-analysis to investigate further the association between vitamin D supplementation and the risk of stroke.MethodsThis meta-analysis was conducted in accordance with the PRISMA statement and included all the randomized controlled trials (RCTs) that analyzed the relationship between v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Despite biological evidence and support from observational studies, recent metaanalyses and systematic reviews [112][113][114][115][116] of RCTs that have assessed the effect of vitamin D supplementation reported that it was not associated with a reduction in the risk of ACM, CVM, MI, stroke, HF, or MACE. A meta-analysis from the US Preventive Services Task Force (USPSTF) [117] included 77 fair-or good-quality RCTs and reported that vitamin D treatment did not affect mortality or CVD incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite biological evidence and support from observational studies, recent metaanalyses and systematic reviews [112][113][114][115][116] of RCTs that have assessed the effect of vitamin D supplementation reported that it was not associated with a reduction in the risk of ACM, CVM, MI, stroke, HF, or MACE. A meta-analysis from the US Preventive Services Task Force (USPSTF) [117] included 77 fair-or good-quality RCTs and reported that vitamin D treatment did not affect mortality or CVD incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Kaul and Manikinda (2021) demonstrated that VD level could work in the risk of stroke, while it could not be regarded as a risk factor for stroke. Fu et al.’s (2022) research indicated that no reduction in stroke risk was observed through supplementary vitamin D intake. Many factors can lead to differences in the effectiveness of supplementing the same dose of vitamin D, such as gender, underlying diseases, and duration of exposure to sunlight (Kennel et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[ 78 ] However, this association was not corroborated by a separate meta‐analysis encompassing 24 RCTs with 86 202 participants, which found no significant protective effect of vitamin D supplementation against stroke risk. [ 79 ]…”
Section: Clinical Evidence On the Role Of Vitamin D In Atherosclerosismentioning
confidence: 99%